## tìm số nguyên x, biết 1, (x + 3) chia hết ( x + 1 ) 2, ( x ² – x + 2 ) chia hết ( x – 1 ) 3, ( 2x + 5 ) chia hết ( x + 2 ) 4, ( x ² + 2x + 4 ) c

Question

tìm số nguyên x, biết
1, (x + 3) chia hết ( x + 1 )
2, ( x ² – x + 2 ) chia hết ( x – 1 )
3, ( 2x + 5 ) chia hết ( x + 2 )
4, ( x ² + 2x + 4 ) chia hết ( x + 1 )
5, ( 3x + 5 ) chia hết ( x – 2 )
…..hết….
giúp em đi ạ

in progress 0
1 năm 2021-10-27T20:13:21+00:00 1 Answers 2 views 0

5) $$\left[ \begin{array}{l} x = 13\\ x = – 9\\ x = 3\\ x = 1 \end{array} \right.$$
$$\begin{array}{l} 1)x + 3 \vdots x + 1\\ \to x + 1 + 2 \vdots x + 1\\ \to 2 \vdots x + 1\\ \to x + 1 \in U\left( 2 \right)\\ \to \left[ \begin{array}{l} x + 1 = 2\\ x + 1 = – 2\\ x + 1 = 1\\ x + 1 = – 1 \end{array} \right. \to \left[ \begin{array}{l} x = 1\\ x = – 3\\ x = 0\\ x = – 2 \end{array} \right.\\ 2){x^2} – x + 2 \vdots x – 1\\ \to x\left( {x – 1} \right) + 2 \vdots x – 1\\ \to 2 \vdots x – 1\\ \to x – 1 \in U\left( 2 \right)\\ \to \left[ \begin{array}{l} x – 1 = 2\\ x – 1 = – 2\\ x – 1 = 1\\ x – 1 = – 1 \end{array} \right. \to \left[ \begin{array}{l} x = 3\\ x = – 1\\ x = 2\\ x = 0 \end{array} \right.\\ 3)2x + 5 \vdots x + 2\\ \to 2\left( {x + 2} \right) + 1 \vdots x + 2\\ \to 1 \vdots x + 2\\ \to x + 2 \in U\left( 1 \right)\\ \to \left[ \begin{array}{l} x + 2 = 1\\ x + 2 = – 1 \end{array} \right. \to \left[ \begin{array}{l} x = – 1\\ x = – 3 \end{array} \right.\\ 4){x^2} + x + x + 4 \vdots x + 1\\ \to x\left( {x + 1} \right) + \left( {x + 1} \right) + 3 \vdots x + 1\\ \to 3 \vdots x + 1\\ \to x + 1 \in U\left( 3 \right)\\ \to \left[ \begin{array}{l} x + 1 = 3\\ x + 1 = – 3\\ x + 1 = 1\\ x + 1 = – 1 \end{array} \right. \to \left[ \begin{array}{l} x = 2\\ x = – 4\\ x = 0\\ x = – 2 \end{array} \right.\\ 5)3x + 5 \vdots x – 2\\ \to 3\left( {x – 2} \right) + 11 \vdots x – 2\\ \to 11 \vdots x – 2\\ \to x – 2 \in U\left( {11} \right)\\ \to \left[ \begin{array}{l} x – 2 = 11\\ x – 2 = – 11\\ x – 2 = 1\\ x – 2 = – 1 \end{array} \right. \to \left[ \begin{array}{l} x = 13\\ x = – 9\\ x = 3\\ x = 1 \end{array} \right. \end{array}$$